2010
DOI: 10.4254/wjh.v2.i12.442
|View full text |Cite
|
Sign up to set email alerts
|

Development of osteomalacia in a post-liver transplant patient receiving adefovir dipivoxil

Abstract: We report the case of a patient treated with living do norrelated liver transplantation who suffered from osteomalacia during adefovir dipivoxil (ADV)containing antiviral therapy for lamivudineresistant hepatitis B virus infection. The patient had generalized bone pain, with severe hypophosphatemia after 20 mo of ADV therapy. Radiographic studies demonstrated the presence of osteomalacia. The peak plasma ADV level was 38 ng/mL after administration of ADV at 10mg/day. It was also found that ADV affected the met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
2

Year Published

2012
2012
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 27 publications
1
11
2
Order By: Relevance
“…Literature review revealed only 12 other cases of hypophosphatemic osteomalacia induced by low‐dose (10 mg daily) ADV (see Table ). The age of these patients varied from 22 to 74 years, with a median of 51·6 years.…”
Section: Details Of the Casementioning
confidence: 99%
See 1 more Smart Citation
“…Literature review revealed only 12 other cases of hypophosphatemic osteomalacia induced by low‐dose (10 mg daily) ADV (see Table ). The age of these patients varied from 22 to 74 years, with a median of 51·6 years.…”
Section: Details Of the Casementioning
confidence: 99%
“…Male: female ratio was 10:3. Most cases (11/13) involved subjects of East‐Asian ethnicity, including Korean, Cambodian, Chinese and Japanese . The other two cases did not specify ethnicity .…”
Section: Details Of the Casementioning
confidence: 99%
“…Nephrotoxicity associated with high-dose ADV typically has a late onset ([6 months) [15]. The time to onset of low-dose ADV-induced FS, based on case reports, ranges from a few months to [5 years [4][5][6][7][8][9][10][11][12]. In our patient, it took more than 2 years before the tubulopathy became apparent.…”
Section: Discussionmentioning
confidence: 99%
“…From the series of case reports so far, the time to resolution after cessation of ADV ranged from a few weeks to months [4][5][6][7][8][9][10][11][12]. A previous trial with high-dose ADV treatment showed a median time to resolution of renal dysfunction of 15 weeks, with the nephrotoxicity failing to resolve completely at 41 weeks after onset in 16 % of the patients [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation